Link between Allais Effect and General Relativity’s Residual Arc during Solar Eclipse - Russell Bagdoo (New Frontiers in Physical Science Research Vol. 8, 2023)
The purpose of this article is to establish a relation between two gravitational anomalies: one that has attracted part of the scientific community, the Allais effect that occurs during solar eclipse; the other, noticed but forgotten by the whole scientific community, the General Relativity’s residual arc of the curvature of rays of light in the solar gravitational field during the same eclipse. There is a systematically observed deflection about 10\(%\) larger than the theoretical value of General Relativity, which coincides with the "eclipse effect" found by Maurice Allais, thrown aside because it upsets the established truths. These corresponding anomalies were never explained by any theories and turn out to be new gravitational physics.